A decade of gem research: Achievements and challenges [Una década de investigación basada en el gem: Logros y retos] (2011)
This paper analyzes the content and the evolution of the research based on the GEM Project (Global Entrepreneurship Monitor). With this aim, a rigorous search of the published articles in the journals included in the Journal Citation Reports (JCR) was made, through an exploratory analysis focused in the articles that have used GEM data. The main findings of the study show that institutional approach is the most useful conceptual framework. Also, although there are still few academic publications using GEM data, the number of articles is increasing in terms of "niches" for future research lines. © 2011 de Cladea.